The factors affecting foreign direct investment for services industry in Malaysia / Uthman Syibli Nazari - Nazari, Uthman Syibli (2022)
More private investment is needed in the services sector in Malaysia's effort to become a high-income economy. Research on the factors that influence foreign direct investment (F DI), particularly in the services industry, is scarce at the national and even at the industry level. The location theory asserts that inflows of FDI into a host country are influenced by the factors such as resources, infrastructure, market conditions, cost, and the business environment. A panel dataset of a few services industries from 1989 to 2019 is used in this study to examine the location theory's validity in Malaysia. The data was analysed using Correlation Analysis, Descriptive Analysis, Normality Test, and Regression Test. inflows of FDI into the services sector have been influenced by market size, inflation rate, communication infrastructure and skilled workers at the industry level. Progress in liberalizing FDI appears to have a minimal effect on the dynamic changes of other variables. Keywords: Foreign Direct Investment (EDI), market conditions, human capital, inflation rate